1993
DOI: 10.1055/s-2007-994761
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli in Papanicolaou Smears, Genital Infections, and Pregnancy

Abstract: Papanicolaou (Pap) smears taken at the first antenatal visit of black African women were examined for lactobacillary expression and its correlation with the prevalence of genital infections and with the outcome of pregnancy. Lactobacillary morphotypes were absent (grade III) in 52% of 256 women. Trichomonas, Chlamydia, gonococci, or syphilis was identified in 54% of grade III women, and in 17% of grade I + II women (p < 0.0001). There were partially independent positive associations of Trichomonas, Chlamydia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 7 publications
5
45
1
1
Order By: Relevance
“…6 Donders also records abnormal status of lactobacilli, that is, their absence, which is a negative factor and enables development of infection, especially in pregnancy. [7][8][9][10][11] In our study most common organism is the E. Coli amounting 34% followed by Candidial spp. 21%.…”
Section: Discussionsupporting
confidence: 50%
“…6 Donders also records abnormal status of lactobacilli, that is, their absence, which is a negative factor and enables development of infection, especially in pregnancy. [7][8][9][10][11] In our study most common organism is the E. Coli amounting 34% followed by Candidial spp. 21%.…”
Section: Discussionsupporting
confidence: 50%
“…Severe complications such as mid-trimester pregnancy losses, chorioamnionitis and even first trimester abortions were linked to the latter flora and mycoplasmata 8,17,18 . McDonald et al 9 found E. coli and group B streptococci to be important pathogens alongside the classical bacterial vaginosis organisms, and we reported that abnormal flora, but not full-blown bacterial vaginosis, was associated with preterm birth 11,19 . We hence suggested that a second abnormality of the vaginal flora should be considered, now termed 'aerobic vaginitis' 1 .…”
Section: Vaginal Fluid Constituentsmentioning
confidence: 54%
“…Treatment with metronidazole was highly unsuccessful in women with aerobic vaginitis (unpublished data) and is the subject of an ongoing treatment trial. The independent relationships of Trichomonas and abnormal flora with preterm birth have been studied in a population with high prevalence of both conditions 19 . Chlamydia and gonorrhoea cervicitis were excluded in the current series.…”
Section: Vaginal Fluid Constituents No Infection Candida Vaginitis Bamentioning
confidence: 99%
“…Using the lactobacillary grading of the vaginal microflora in a population with high prevalence of genital infection [4,5], we previously demonstrated the link between nonspecific disturbance of the vaginal flora early in pregnancy and first trimester miscarriage, preterm birth and low birth weight [6][7][8][9][10]. The association of (anaerobic) bacterial vaginosis and preterm birth has been repeatedly confirmed [11][12][13][14][15], and treatment with oral clindamycin [12,14], or oral metronidazole [16] has proven to be effective in delaying delivery.…”
Section: Introductionmentioning
confidence: 99%